Cyclicality of Job and Worker Flows: New Data and a New Set of Stylized Facts - Felix Maximilian Wellschmied; Rüdiger Bachmann; Christian Bayer; Stefan Seth (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We study the relationship between cyclical job and worker flows at the plant level using a new data set spanning from 1976-2006. We find that procyclical labor demand explains relatively little of procyclical worker flows. Instead, all plants in the employment growth distribution increase their worker turnover during booms. We also find that cyclical changes in the employment growth distribution are mostly driven by plants moving from inactivity to a growing labor force during booms. Consequently, increased labor turnover at growing plants is the main quantitative driver behind increased labor turnover during booms. We argue that on the job search models are able to capture non-parallel shifts in the employment growth distribution and procyclical conditional worker flows for a range of the growth distribution. Yet, they fail to rationalize procyclical accession rates for all shrinking and procylical separation rates for all growing plants.
Keywords: E32; J23; J63; 330